2011
DOI: 10.1098/rsfs.2011.0021
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-mediated optical tomography: a review of current methods

Abstract: Ultrasound-mediated optical tomography (UOT) is a hybrid technique that is able to combine the high penetration depth and high spatial resolution of ultrasound imaging to overcome the limits imposed by optical scattering for deep tissue optical sensing and imaging. It has been proposed as a method to detect blood concentrations, oxygenation and metabolism at depth in tissue for the detection of vascularized tumours or the presence of absorbing or scattering contrast agents. In this paper, the basic principles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
75
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 97 publications
0
75
0
Order By: Relevance
“…This has been utilised in ultrasound modulated optical tomography (also called acousto-optic imaging) to image local tissue optical properties at millimetre to centimetre depth. Recent reviews of this topic can be found in (Wang 2004;3 Tang et al 2010;Daniel S. Elson et al 2011). Simulation results have shown that by using temporally coherent light and detecting the phase change of diffuse photons from tissue, tissue displacement at the level of nanometres can be detected (Li et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This has been utilised in ultrasound modulated optical tomography (also called acousto-optic imaging) to image local tissue optical properties at millimetre to centimetre depth. Recent reviews of this topic can be found in (Wang 2004;3 Tang et al 2010;Daniel S. Elson et al 2011). Simulation results have shown that by using temporally coherent light and detecting the phase change of diffuse photons from tissue, tissue displacement at the level of nanometres can be detected (Li et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Tagging photons using ultrasound is a method to map the optical properties of thick scattering media such as biological tissues [1]. In order to detect the ultrasonically tagged photons coming out of a scattering sample, dynamic holographic techniques are frequently used.…”
mentioning
confidence: 99%
“…A major challenge towards quantification of optical absorption is to compensate the signal strength of photoacoustics for local fluence variations. Recently fluence compensation of PA signals was proposed by using acousto-optic (AO) imaging [17,104] in combination with PA [7]. This method relies on the principle that both PA and AO signal strength depend on the local fluence.…”
Section: Introductionmentioning
confidence: 99%
“…In this review we describe the progress made in AO imaging since the previous review by Wang [1] in 2003: theoretical models, the detection methods to detect the tagged photons, and applications of AO imaging. For further reading, a review by Elson et al [17] is also focusing on the detection methods, scanning and applications. They give however no equations from the models in the modeling section.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation